Lipoprotein levels and statin treatment related to dementia and cognitive decline in individuals with type 2 diabetes : an observational analysis from the ADVANCE study - af Geijerstam, Peder; Chalmers, John; Pikkemaat, Miriam ; 0000-0002-9808-207X; Peters, Ruth; Marre, Michel; Mancia, Giuseppe; Woodward, Mark; Harris, Katie (Cardiovascular Diabetology, 2025)
Introduction: Studies on the association between lipid levels and lipid-lowering treatment and the risk of dementia and/or cognitive decline (CD) have shown conflicting results and are few in individuals with type 2 diabetes (T2D). The aim was to evaluate the relationship of baseline LDL cholesterol levels and statin treatment with the development of dementia/CD in patients with T2D from the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation trial. Methods: Dementia was diagnosed using the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV), and CD was defined as at least a 3-point decrement in the Mini Mental State Examination score. Exposures were baseline LDL cholesterol levels, statin treatment at baseline, and statin treatment initiation during the first 18 months of follow-up. Multinomial logistic regression was used to estimate the odds ratio (OR) and 95% CI for the composite of dementia/CD. Results: Of 11,140 participants, 1827 (16.4%) developed dementia/CD over the 5-year follow up. The OR (95% CI) of dementia/CD were 1.06 (1.00–1.14) per standard deviation higher in baseline LDL cholesterol and 0.90 (0.79–1.03) for participants with vs without statin treatment. Conclusion: We observed an association between LDL levels, but not statin treatment, and incident dementia/CD. Although causality cannot be determined by our study, the results are in line with multiple randomised controlled trials. However, to understand the long-term effects of lipid levels and statin treatment on dementia/CD, studies of longer follow-up are still needed.
Keywords: Cholesterol; Cognitive decline; Dementia; Diabetes; Diabetes complications; Lipids; Lipoproteins; Type 2 diabetes